Luz Negib: el arte figurativo en Caperucita y los lobos - Núñez Núñez, Maria Eugenia (2025)
Luz Negib has a pictorial body of work spanning four decades since 1950s in Lima. She introduced the use of irony and humor in Peruvian visual arts to reveal circumstances and attitudes within Peruvian society, beneath the seemingly anecdotal nature of her themes. In terms of artistic style, she embraced figuration at a time when abstraction was the undisputed avant-garde and symbol of modernity. The series Little Red Riding Hood and the wolves, a children’s tale, serves as a pretext for Negib to present a Little Red Riding Hood who becomes the victimizer of wolves that are her suitors. In the 13paintings of the series, she subtly critiques traditional machismo and certain hierarchies and behaviors within our society. I consider her an important artist because she has a unique perspective that challenges the imposed narrative. She appropriates a familiar story and masterfully unveils contemporary issues of her time, ones that had never before been addressed in art.